Advances in the study of axon–associated vesicles - Liu, Yanling; Shuai, Ke; Sun, Yiyan; Zhu, Li; Wu, Xiao-Mei (Frontiers in Molecular Neuroscience, 2022)
The central nervous system is the most important and difficult to study system in the human body and is known for its complex functions, components, and mechanisms. Neurons are the basic cellular units realizing neural functions. In neurons, vesicles are one of the critical pathways for intracellular material transport, linking information exchanges inside and outside cells. The axon is a vital part of neuron since electrical and molecular signals must be conducted through axons. Here, we describe and explore the formation, trafficking, and sorting of cellular vesicles within axons, as well as related-diseases and practical implications. Furthermore, with deepening of understanding and the development of new approaches, accumulating evidence proves that besides signal transmission between synapses, the material exchange and vesicular transmission between axons and extracellular environment are involved in physiological processes, and consequently to neural pathology. Recent studies have also paid attention to axonal vesicles and their physiological roles and pathological effects on axons themselves. Therefore, this review mainly focuses on these two key nodes to explain the role of intracellular vesicles and extracellular vesicles migrated from cells on axons and neurons, providing innovative strategy for future researches.